2022
DOI: 10.18063/ijb.v8i3.556
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Multi-Morphology Bone-like Porous Scaffolds: Experiments and Micro-Computed Tomography-Based Finite Element Modeling Approaches

Abstract: Tissue engineering, whose aim is to repair or replace damaged tissues by combining the principle of biomaterials and cell transplantation, is one of the most important and interdisciplinary fields of regenerative medicine. Despite remarkable progress, there are still some limitations in the tissue engineering field, among which designing and manufacturing suitable scaffolds. With the advent of additive manufacturing (AM), a breakthrough happened in the production of complex geometries. In this vein, AM has enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…4DP of intelligent/smart materials has been utilized to develop soft devices such as sensors, actuators, robotics, and grippers for a wide range of engineering applications, as illustrated in Figure 12. The main goal of 4DP is to develop multi-functional and smart devices, for these applications [264]. This section incorporates various engineering and biomedical applications of 4D-printed robotics.…”
Section: Applications Of 4d-printed Smart Materialsmentioning
confidence: 99%
“…4DP of intelligent/smart materials has been utilized to develop soft devices such as sensors, actuators, robotics, and grippers for a wide range of engineering applications, as illustrated in Figure 12. The main goal of 4DP is to develop multi-functional and smart devices, for these applications [264]. This section incorporates various engineering and biomedical applications of 4D-printed robotics.…”
Section: Applications Of 4d-printed Smart Materialsmentioning
confidence: 99%
“…However, such complicated architectures require precise fabrication techniques (Abdelaal and Darwish, 2012). Fortunately, by emerging and developing additive manufacturing (AM), the fabrication of complicated structures has been facilitated (Contessi Negrini et al, 2022;Noroozi et al, 2022a;Noroozi et al, 2022b;Shirzad et al, 2021). Hence, numerous researchers have combined AM techniques with biomedical engineering to fabricate auxetic bone implants such as femoral bone implants and bone screws.…”
Section: Introductionmentioning
confidence: 99%
“…Raney et al even reported the inducing of an angle of the fibril alignment by applying a spinning motion to the nozzle [ 11 ]. Moreover, Noroozzi et al (2021) showed how, in 3D printing, the geometry of the printed material also strongly influenced the final material properties, adding an additional level to the hierarchical structure of the material [ 12 ].…”
Section: Introductionmentioning
confidence: 99%